DESIGN AND IMPLEMENT OF POLLUTION ALARM SYSTEM - Samer Bashar Mohaisen Ali (Journals Park Publishing, 2024)
The escalating concerns surrounding environmental pollution necessitate the development of robust monitoring systems capable of detecting various pollutants in real-time. This project presents the design and implementation of a Pollution Alarm System (PAS) aimed at addressing these challenges. The system comprises a network of sensors, including temperature, humidity, gas, air quality, sound, and ambient light sensors, integrated with a microcontroller (ESP32). Upon data collection, the system processes and analyzes the information to identify abnormal pollution levels, triggering alarms when predefined thresholds are exceeded. This abstract provides an overview of the proposed system's components, functionalities, and objectives, offering insights into its potential contributions to environmental monitoring and public health. Through rigorous testing and evaluation, the effectiveness and reliability of the PAS in detecting and alerting about pollution anomalies will be assessed, ultimately contributing to the advancement of pollution monitoring technology and environmental sustainability efforts.’
Keywords: Pollution Monitoring, Environmental Sensors, Real-time Detection, ESP32 Microcontroller, Public Health Alert System.